First report of white mold caused by Sclerotinia sclrotiorum on zinnia (Zinnia elegans) in Bangladesh (Bangladesh Journal of Agricultural Research, 2026)
Abstract not availableBangladesh J. Agril. Res. 47(4): 473-476, December 2022